SPECIES OF EMERGENCE. - Peterson, Gregory R. (Zygon: Journal of Religion & Science, 2006)
The category of emergence has come to be of considerable importance to the science-and-religion dialogue. It has become clear that the term is used in different ways by different authors, with important implications. In this article I examine the criteria used to state that something is emergent and the different interpretations of those criteria. In particular, I argue similarly to Philip Clayton that there are three broad ranges of interpretation of emergence: reductive, nonreductive, and radical. Although all three criteria have their place, I suggest that the category of radical emergence is important both for science and theology.